Rectovaginal Fistula Due to Missing Intra Uterine Contraceptive Device (Nepal Journal of Obstetrics and Gynaecology, 2018)
Rectovaginal fistula is an abnormal communication between the rectum and the vaginal. This leads to uncontrollable passage of feces and flatus through the vagina. It therefore causes distressing physical, social and psychological symptoms on the affected woman. The commonest cause of Rectovaginal Fistula is obstetric trauma commonly in developing countries with poor access to Obstetric care or substandard care provision. The case reported here highlights a rare situation in which a birth control measure of Intrauterine Contraceptive Device (IUD) in a 36 years old healthy female leads to a high Rectovaginal fistula.Keywords: fecal incontinence, missing IUD, rectovaginal fistula